Circumpolar Indigeneity in Canada, Russia, and the United States (Alaska): Do Differences Result in Representational Challenges for the Arctic Council? - Sidorova, Evgeniia (ARCTIC, 2019)
This article investigates differences in circumpolar indigeneities in three major Arctic nations: Russia, Canada, and the United States (Alaska). Russia has different ways of recognizing indigeneity in law, and that definition of indigeneity excludes larger Indigenous groups of the Far North (Sakha, Komi), rather than seeing them as ethnic (titular) minorities. This study reveals that: 1) not all Indigenous peoples are represented in the Arctic Council; 2) there are historical explanations for this underrepresentation; 3) the Arctic Council should include more Indigenous groups as Permanent Participants. The equal representation of Indigenous organizations as Permanent Participants in the Arctic Council is important because all Indigenous groups in the Arctic should be heard. Cet article tente de déterminer s’il y a une différence entre les indigénéités circumpolaires de trois grands acteurs de l’Arctique, soit: la Russie, le Canada et les États-Unis (Alaska). En raison de la différence en matière de reconnaissance juridique de l’indigénéité en Russie, la définition de l’indigénéité exclut les grands groupes indigènes du Grand Nord (Sakha, Komi) et les considère plutôt comme des minorités ethniques (titulaires). Cette étude révèle que: 1) ce ne sont pas tous les peuples indigènes qui sont représentés au Conseil de l’Arctique; 2) cette sous-représentation s’explique par des raisons historiques; et 3) le Conseil de l’Arctique devrait inclure plus de groupes indigènes à titre de participants permanents. La représentation égale des participants permanents (organisations indigènes) au Conseil de l’Arctique est importante, car tous les groupes indigènes de l’Arctique devraient avoir la possibilité de se faire entendre.